IJCM_94A: Risk Factors for Short Birth Intervals in women: A Case-Control Study from a Tertiary Health Care facility in Central India - Shingnad Saurabh; Wadhva Sarita; Narlawar Uday (Wolters Kluwer Medknow Publications, 2024)
Background: The interval between successive pregnancies, commonly referred to as the birth interval, plays a crucial role in maternal and child health outcomes. Optimal birth spacing is associated with improved maternal nutritional status, reduced risks of adverse pregnancy outcomes, and enhanced child survival. Conversely, short birth intervals, defined as intervals less than 24 months between two consecutive live births, have been linked to an increased likelihood of adverse maternal and child health consequences. Through a comprehensive examination of the contextualized risk factors, we aim to provide evidence that can guide healthcare practitioners, policymakers, and public health professionals in their efforts to improve maternal and child health outcomes in Central India. Objective: To determine risk factors for short birth interval among women in the tertiary health care centre of Central India. Methodology: A hospital-based unmatched case-control study was employed on 45 cases and 45 controls. Cases were women who gave birth within the last 6 months and with at least two consecutive alive births with a birth interval of less than 33 months. Controls were women who gave birth within the last 6 months and had a birth interval between 33 to 59 months between two successive live births. The data was collected by predesigned and pretested semi structured questionnaire from selected respondents. Results: Some important risk factors identified in the present study were age less than 30 years, use of contraception and shorter duration of breastfeeding. Conclusion: Encouraging postpartum family planning and effective breastfeeding will go a long way to reduce the prevalence of short birth interval and its consequences on maternal, neonatal and child health